Effects of diode laser application on inflammation and mpo in periodontal tissues in a rat model - USLU, Mustafa Özay (J Appl Oral Sci, 2018)
OBJECTIVE: In this study, we aimed to histologically and immunologically evaluate the effect of diode laser treatment when applied adjunctive to scaling and root planing (SRP) in an experimental periodontitis model. MATERIALS AND METHODS: We used Wistar-Albino rats (n=60) with average weight of 230 g. Experimental periodontitis was induced by ligature at the right and left first mandibular molar teeth in all rats. After 11 days, the ligature was removed and rats were divided into two groups. The control group (n=30) received only SRP treatment, while the laser group (n=30) received a diode laser (GaAlAs, 810 nm, 1 W, 10 J, 20 s) treatment adjunctive to SRP. Ten rats in each group were sacrificed after 7, 15, and 30 days. Histopathological examination was performed in the left mandible of rats. Myeloperoxidase (MPO) was evaluated by western blot in the gingival specimens from the right mandible. RESULTS: MPO levels in the laser group were statistically significantly lower compared with the control group (p≤0.05). There was no statistically significance at any time between MPO levels in the control group (p>0.05). MPO levels in the laser group at the 7(th) day were statistically significantly higher compared to the 15(th) (p≤0.05) and the 30(th) day (p≤0.05). Inflammatory cell infiltration decreased over time in both groups and was statistically significantly lower in the laser group than in the control group at all times (p≤0.01). CONCLUSIONS: Within the limits of this study, we suggest that diode laser application is an adjunctive treatment because it reduced inflammation and MPO when applied in addition to SRP. On the other hand, more studies are needed for the assessment of the effects of diode laser application to periodontal tissues.